Pengaruh Pelatihan Kerja, Motivasi, Stres Kerja, dan Benefit Kerja Terhadap Loyalitas Pegawai - Silalahi, Dinda Sari Margaretha; Nadapdap, Kristanty; Purba, Jon Hendri (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine how much influence job training, motivation, job stress, and job benefits have on employee loyalty at the PT Pegadain rantauprapat branch office. The research method used in this research is quantitative descriptive research method. The sample in this study were 30 respondents. The data analysis method used is multiple linear regression analysis. Based on the results of the t hypothesis test it can be concluded that job training partially affects job loyalty Based on the results of the t hypothesis test it can be concluded that motivation partially affects job loyalty, partial job stress does not always have a significant effect on job loyalty, job benefits partially affect job loyalty. Based on the results of the F hypothesis test, it can be concluded that job training, motivation, work stress, and work benefits simultaneously affect employee loyalty. Based on the results of the coefficient of determination analysis, the Adjusted R Square value is 0.594 or 59.4%. So it can be concluded that the effect of job training, motivation, work stress, and work benefits on employee loyalty is 59.4%, the remaining 100%-59.4% = 40.6% is the influence of other variables or factors.